2015
DOI: 10.1016/j.aprim.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Estudio ARAPOC: prevalencia de síntomas respiratorios y enfermedad obstructiva crónica en población general

Abstract: The high prevalence of COPD and the significant level of underdiagnoses lead to believe that early diagnosis of this disease is still a pending issue. New strategies need to be developed to resolve this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Previous studies have shown that multimorbidity is generally more prevalent in women than in men. 4 Asthma tends to be more prevalent in women than in men, 27 whereas historically COPD tended to have the opposite gender balance, 28 although there is evidence that this trend is starting to reverse. 29 , 30 To date, however, there is no clear evidence of a difference in the rates of comorbidity by gender, specifically in those with asthma.…”
Section: Gendermentioning
confidence: 99%
“…Previous studies have shown that multimorbidity is generally more prevalent in women than in men. 4 Asthma tends to be more prevalent in women than in men, 27 whereas historically COPD tended to have the opposite gender balance, 28 although there is evidence that this trend is starting to reverse. 29 , 30 To date, however, there is no clear evidence of a difference in the rates of comorbidity by gender, specifically in those with asthma.…”
Section: Gendermentioning
confidence: 99%
“…Tamayo-Marco et al ( 56 ) reported a proportion of unknown cases of diabetes nearly 50% in their Aragonese sample population. It is also worth mentioning that, in the specific case of Aragon, there has also been talk of under-diagnosis of other NCDs such as Chronic Obstructive Pulmonary Disease ( 57 ) and depression ( 58 ). Regarding the VMP, in Spain there are previous initiatives such as the Atlas of VMP in the Spanish National Health System ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Para nuestros trabajos de fin de grado de medicina, hemos realizado un estudio descriptivo de la correlación entre los indicadores de prevalencia del tabaquismo y de la morbimortalidad por la enfermedad pulmonar obstructiva crónica (EPOC) en España durante 20 años, a partir de los artículos publicados en su revista1, 2. Hemos evaluado, también, la evolución de los mismos indicadores por cardiopatía isquémica en España, utilizando los datos del portal estadístico del Sistema Nacional de Salud 3 , y la información de diferentes fuentes: Encuesta Nacional de Salud de España (ENSE), Encuesta Europea de Salud (EES), Conjunto Mínimo Básico de Datos (CMBD) y Defunciones Según Causa de Muerte (DSCM).…”
unclassified